2022
DOI: 10.1029/2022jb024517
|View full text |Cite
|
Sign up to set email alerts
|

Third‐Order Padé Thermoelastic Constants of Solid Rocks

Abstract: Classical third‐order thermoelastic constants are generally derived from the theory of small‐amplitude acoustic waves in isotropic materials during heat treatments. Investigating higher‐order thermoelastic constants for higher temperatures is challenging owing to the involvement of the number of unknown parameters. These Taylor‐type thermoelastic constants from the classical thermoelasticity theory are formulated based on the Taylor series of the Helmholtz free energy density for preheated crystals. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Various authors have shown latitudinal and longitudinal ionosphere responses due to PPEF [60][61][62][63][64]. EEJ variations at different longitudes are due to the underlining effects of local winds, which are responsible for EEJ driving [65][66][67][68][69]. In addition, longitudinal differences in EEJ are caused by the different nature of the propagating diurnal tides, the meridional winds, and the dynamics of the migratory tides [70][71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have shown latitudinal and longitudinal ionosphere responses due to PPEF [60][61][62][63][64]. EEJ variations at different longitudes are due to the underlining effects of local winds, which are responsible for EEJ driving [65][66][67][68][69]. In addition, longitudinal differences in EEJ are caused by the different nature of the propagating diurnal tides, the meridional winds, and the dynamics of the migratory tides [70][71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…As is known, the research related to the building sector covers a wide range of subjects from construction safety [47,48] and material analysis [49,50] to energy systems. In this work, the focus was on energy performance analysis that was successfully carried out using sophisticated machine learning.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical properties of foundation materials affect the stability of civil and mining structures [36,37]. Mineralogical and physical properties have a significant effect on the mechanical properties and stability of mines [38].…”
Section: Geo-mechanical Properties Of Samplesmentioning
confidence: 99%